Innovative Work Behavior: A Strong Combination of Leadership, Learning, and Climate - Sutardi, Didi; Nuryanti, Yulis; Kumoro, Dwi Ferdiyatmoko Cahya; Mariyanah, Siti; Agistiawati, Eva (IJOSMAS, 2022)
The main objective of this research is to investigate the effect of innovation climate, learning capability, and transformational leadership on innovative work behavior. The sample of this research was taken from 102 lecturers of a private university in Indonesia using a simple random sampling technique and using SEM (Structural Equation Model) with SmartPLS version 3.0 software as a statistical tool. The results of this study state that all hypotheses are supported and it is found that innovation climate, learning capability, and transformational leadership have a positive and significant effect on innovative work behavior. The novelty of this research finding is that it is successful in combining individual, organizational, and environmental level variables in higher education that influence innovative work behavior among private higher education lecturers.